#TITLE_ALTERNATIVE# - SYANI INDRA SUTARSA (NIM 12403016), ARDEN
The travel time with respect to the offset due to a dipping and undulating reflector is shorter than it is on horizontal one. It is shown by slope slighter hyperbolic curve. Therefore, its velocity seems faster than the true velocity. Travel time function can be expanded using Taylor series up to second order that contain of interface curvature implicitly. This hyperbolic curve is called the Common Reflection Surface stacking curve (CRS stacking curve). Using this hyperbolic curve bad velocity picking can be avoided. In this research, the CRS parameters are obtained by forward modelling. CRS parameters searched using raytracing along the horizon in geological model. From the experiment, that the CRS hyperbolic curve fits data better than conventional hyperbolic curve does. Semblances show that the maximum energy on CRS stack gives a true velocity rather than on conventional stack. Real data semblances streached as increasing depth, it is caused by incorrect CRS parameters that obtained by forward modelling. The NMO correction result and seismic image show the velocity picking accuracy and data curve fitness. The CRS NMO correction result show streatching effect lest then conventional NMO correction result. The CRS Seismic image result show clearer, more focus event and contain higher frequency then the conventional seismic image.